Analisis Hukum Pembuktian Tindak Pidana Judi Bola Online Berdasarkan Undang Undang No 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik - Mohd Fariz Lihara; Khomaini Khomaini; Tengku Mabar Ali (CV. Rayyan Dwi Bharata, 2025)
Problems in this study How is the criminal offense of online ball gambling based on uu no 19 of 2016 concerning information and electronic transactions, How is law enforcement against online gambling crimes in terms of uu no 19 of 2016 information and electronic transactions and How is the context of evidence of online gambling games associated with the law of evidence against the criminal offense in question. This research uses legal analysis theory from previous researchers, journals and books written by experts. The research method uses qualitative research. Research Results and Discussion: The crime of online ball gambling based on Law No. 19 of 2016 concerning information and electronic transactions, Law enforcement against online gambling crimes in terms of Law No. 19 of 2016 concerning information and electronic transactions and the context of evidence of online gambling games associated with the law of evidence against the criminal act in question. The conclusions and suggestions in this study are that prevention efforts are needed by blocking sites that have gambling content as part of the police's efforts to eradicate online gambling crimes. Law enforcers must do more socialization to the public about the dangers of online gambling crimes.